Sistema reprodutivo e biologia floral de Xylopia brasiliensis Spreng., em Lavras - MG - Andrade, Bruno Moraes de (1993)
With the purpose of evaluating the reprodutive system of Xylopia brasiliensis Spreng., aspects of breeding systems were assessed, complemented by the observations of phenology and floral biology on trees planted in the Forest Nursery at the Escola Superior de Agricultura de Lavras (ESAL) MG (21º 14’S, 45º 00' W and 919 m in height), over the period September, 1991 through December, 1992). This species occurs. as trees quite common in semi-deciduous forests from Bahia to Santa Catarina. Blossoming is associated to climatic factors, occuring in rainy season. The inflorescence are axillary. Sub-fasciculate, short-pedunculate occurs on young twigs and owns two to five blossoms. The blossoms are both hermaphrodite and protogynical. The fruit is a multifollicule made up of clustering of small mericarps and is able to replace black pepper as spice, according to several authors' reports. Visiting insects on the blossoms were of the following species of Coleoptera: Macrodactylus pumilis Burm., M. Suturalis Mann., Barybas sp., Acanthinus sp, Brachypnoca venustula Lef.and B. nana Klug. With the exception of species of Brachypnoca, the presence of pollen was not ascertained in the other species, only portions of floral tissues. The presence of beetles, allied to the details of the blossoms, characterize the syndrome of cantharophily for this species. In order to detect breeding system, field trials were undertaken with the following treatments: open-pollinization (PAB-CONTROL); cross-pollinization (PCR), emasculated flowers closed with tulle bags (FFI) self pollinization with pollen of the same tree (AMA) and flowers only emasculated (AGA). Fruit-setting was achieved mainly in the OPP and CRP and in a low amount m the STP treatment. That characterizes to X. brasiliensis, a breeding system preferentially allogamic, being possible to exist an alternative strategy for a small fruit setting through selfing. Cross-pollinization was favored both by protogyny and probably self-incompatibility.